Intravitreal bevacizumab for pediatric exudative retinal diseases - Salman, Abdelrahman G. (Elsevier, 2011)
PURPOSE: To detect if intravitreal bevacizumab can reduce retinal exudation, improve visual and anatomical outcomes, and facilitate the treatment in various pediatric exudative retinal diseases. PATIENTS AND METHODS: Prospective, non-randomized, case series of nine eyes of pediatric exudative retinal diseases less than 18 years old which included six eyes with juvenile diabetic retinopathy, two eyes in children with Coats’ disease, and one eye with myopic choroidal neovascular membrane (CNV). All eyes received only intravitreal bevacizumab injection 1.25 mg/0.05 ml as the primary treatment. The need for adjuvant ablative procedures, including laser photocoagulation or cryotherapy, were performed and recorded. The need for supplementary intravitreal bevacizumab injection was recorded. The changes in pre- and post-operative best-corrected visual acuity (BCVA) and central macular thickness (CMT) were recorded. Serial optical coherent tomography (OCT) and fundus flourescein angiography (FFA) were performed to follow treatment efficacy. RESULTS: The study included 19 eyes of 11 patients with age equal to or less than eighteen years with exudative retinal diseases including type I DM (n = sixteen eyes), Coats’ disease (n = 2 eyes), and due to myopic CNV (n = 1 eye). Mean pre-injection log MAR for all was 0.605 ± 0.174 and mean post-injection for all log MAR was 0.284 ± 0.247. While Mean pre-injection log MAR for DR and myopic CNV patients was 0.576 + 0.152 SD and mean post-injection log MAR for DR and myopic CNV patients was 0.229 + 0.189 at one year. Serial OCT measurements showed that mean CMT for all eyes was 355.8 ± 35.3 μm SD at baseline, which was decreased to 222.42 + 26.2 μm SD. The two eyes of Coats’ disease needed another two supplementary intravitreal bevacizumab injections. No ocular or systemic complications related to bevacizumab were noted during the entire course of follow-up. CONCLUSION: Intravitreal bevacizumab appears to be a well-tolerated treatment for pediatric age group with various exudative retinal diseases. It has the potential as an adjuvant therapy for ablative procedures to improve final visual and anatomical outcome.